Outcome of pregnancy in previous caesarean section: an observational study - Thobbi, Vidya A.; Zeba, Syeda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Presently, good obstetrics means an uncomplicated antenatal period, labour and puerperium for the mother and birth of a healthy body. Post caesarean section pregnancy has now become one of the most common high-risk cases tackled at any hospital. In this paper an attempt has been made to assess the outcomes of pregnancy in previous caesarean section. Methods: This study was conducted among patients in the department of gynecology and obstetrics at Al-Ameen Hospital from June 2016 to December 2018. For that purpose, a sample size of 100 was considered. Data were analyzed using SPSS software v. 23.0. and Microsoft office 2007. Results: The incidence of caesarean section was 10.25%. Anaemia, pregnancy-induced hypertension and diabetes mellitus found in this study is more coincidental. Placenta previa cases were also present. Cephalopelvic disproportion was the commonest indication of the previous section in this study. 20% of the cases have had their previous section due to cephalopelvic disproportion. 18% of the cases had delivered vaginally, 15 cases were delivered by forceps (72.2%) and 3 cases were delivered normally (27.8%). Maternal morbidity was found to be low and there was no maternal death. Conclusions: The patient whose primary section was done due to cephalopelvic disproportion should be assessed thoroughly in her current pregnancy before placing her to elective repeat section. As there is always the possibility of scar rupture in a case of post caesarean section pregnancy one must think twice before doing the primary section. More research is required to evaluate optimum time of management.